Faktor-Faktor Yang Berhubungan Dengan Penyakit Skabies Di Asrama Putra Pondok Pesantren Pancasila Bengkulu Tahun 2019 - Epina Felizita; Kartika Murya Ningrum (JMNS, 2021)
The health system in Indonesia needs a platform that can build and improve the education system and health services not only in cities but also in remote areas. It is supported by one of the state universities in Indonesia, namely Padjadjaran University which is one of the universities that has the feasibility of human resources and other support for the implementation of PKM activities. The purpose of this Community Service activity, Padjadjaran University wants to develop one of the guided villages of Padjadjaran University, namely Arjasari Village so that the community is more concerned about tackling health problems, especially cancer because its spread has undermined even rural communities. The method used is health education and early detection of cervical cancer which is held free of charge for women in Arjasari Village. The results of this PKM show that the age characteristics of women who attend counseling and early examination of cervical Ca are 46-55 years old as many as 23 people (38.33%).